A chemical study of the avocado (Persea americana Mill) with special reference to the fatty oil - Manotok, Clara 1914-
Purpose of the research: To undertake phytochemical study of the fruit of the avocado (Persea americana Mill); to obtain the fatty oil from the different parts of the fruit for study; to look into the utilization of the avocado fatty oil in pharmacy. After a thorough review of the literature on the chemical study of the fruit of avocado with special reference to the fatty oil, a chemical examination of the avocado fruit, especially the pulp and the seed was made. A comparative study was done of the yield of fatty oil, from a number of varieties of avocado especially those varieties found in Talisay Avocado Orchard, Talisay, Batangas. The physical and chemical properties of the different samples of fatty oil obtained from several lots of avocado secured from Magnolia Dairy Products and the Talisay Avocado Orchard, Talisay, Batangas, were undertaken. The fatty oil obtained was employed in making a number of pharmaceutical products. Approximate amount of time devoted to research was about twelve months. Whenever possible, the candidate was allowed to work independently giving her every opportunity to develop herself in research work. This is the first work that has been undertaken in the Philippines on the obtention of the fatty oil from several lots of avocado and from a number of varieties of fruit collected from plants grown in the Philippines. The fatty oil obtained was characterized and its use for the manufacture of a number of pharmaceutical products was studied. The results show that in addition to the present use of avocado in the Philippines, it can also serve as a source of fatty oil which can be utilized in pharmacy and for other purposes.
Available to the general public.
Thesis (Master of Science in Pharmacy)--University of the Philippines, 1941.
Keywords: Plants -- Analysis; Avocado